ON THE ENDOPHRAGMAL SKELETONS OF SPINY LOBSTERS PANVLIRUS HOMARUS AND P. ORNATUS - Pearl, Thomas Mary; Reddy, P Sita Rami; Thangavelu, R (Indian Journal of Fisheries, 2011)
Endophragmal skeletons of P. homariis'and P. ornatus have been describedin detail for the first time. "Subantennal apodeme", 'epistomal apodeme' and'cephalic apodeme' revealed, distinct differences between P. homarus and P.ornatus. "Subantennal apodeme" and "Interparaphragmal apodeme" have beententatively named for the first time. The utility of endophragmal skeleton as ataxonomical tool in the lobsters has been indicated.